The uses of outcome measures within multidisciplinary early childhood intervention services: a systematic review. - Calder, S.; Ward, Roslyn; Jones, M.; Johnston, J.; Claessen, M. (Informa Healthcare, 2017)
Purpose of the article: To review the use of outcome measures, across the domains of activity, participation, and environment, within multidisciplinary early childhood intervention services. MATERIALS AND METHODS: A systematic literature search was undertaken that included four electronic databases: Medline, CINAHL, EMBASE, and the Cochrane Library and Cochrane Database of Systematic Review. Inclusion criteria were age 0-24 months, having or at risk of a developmental disability, in receipt of multidisciplinary early childhood intervention services, and included outcome measures across all domains of the International Classification of Functioning-Child & Youth (ICF-CY). Only peer-reviewed journal articles were considered. Eligible studies were coded using the Oxford Levels of Evidence. Methodological quality was assessed using the Physiotherapy Evidence Database (PEDro) Scale for randomised controlled trials and the QualSyst for non-randomised control trials. RESULTS: Of the total of 5764 records identified, 10 were considered to meet inclusion criteria. CONCLUSION: Fourteen outcome measures were identified, addressing the domains of activity, participation, and environment. Of these, eight have been recommended in the early intervention literature. While the methodological quality of the 10 studies varied, these papers make a contribution to the body of research that acknowledges the role of routine and enriched environments. Implications for Rehabilitation Core practice elements of multidisciplinary early childhood intervention services indicate it is necessary to select outcome measures framed within the International Classification of Functioning-Child & Youth to inform clinical decision-making for measuring intervention effectiveness across the domains of activity, participation and environment. Of the identified measures, three (Canadian Occupational Performance Measure, Pediatric Evaluation of Disability Inventory, and Goal Attainment Scaling) are well-established and identified in the literature as multidisciplinary outcome measures for children with developmental disability. The selection of an appropriate outcome measure depends on the age of the child, individual goals of the family, and the type of intervention. This requires the combination of measures as no one measure alone will capture all components of the International Classification of Functioning-Child & Youth.